Development of a Model for Enhancing the Learning Skills of Students in Early Childhood Education using a Community-based Case Study on Child Development Centers in Nakhon Nayok Province - ชาวระนอง, ชัยยศ (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
This research aims to develop a model for enhancing the learning skill of Students in Early Childhood Education using community-based learning. For the developing of the model, a case study of child development centers in Nakhon Nayok province has been conducted. Later a broader study throughout the central region of Thailand has been conducted in order to assess the effectiveness of the model. The research methodology consists of two steps: 1) Developing the model using document synthesis and an in-depth interview with fifteen experts in early childhood education management using a structured interview. The suitability of the model was examined by 10 experts forming a focus group. Then the feasibility of applying the model in educational management has been examined using questionnaires. The population was 156 people, consisting of the heads of child development centers and academic officers under the jurisdiction of the local administrative organization, Nakhon Nayok Province. 2) The effectiveness of the model has been examined by using confirmatory factor analysis of a sample group of 560 people, which derived from multi-stage sampling, consisting of the heads of child development centers in the central region. The questionnaire with 50 questions had a reliability value of 0.98. The findings are as follows: The model is suitable. It consists of 3 main components and 9 sub-components. The first main component is preparation, which includes 1) a community potential analysis, 2) a curriculum preparation/learning management plan, 3) teacher readiness preparation and 4) educating parents. The second main component is learning management, consisting of 1) physical and movement development, 2) emotional and mental aspects 3) social aspects and 4) intelligence. The third main component is learning assessment. The indicators for all components range in the average between 3.62 - 4.28, and hence show the suitability of the developed model. 2. The efficiency of the model was consistent with the empirical data based on the chi-square value 23.65, with 16 degrees of freedom and a probability value of .09. Every variable component is positive, with values ranging from 0.89 to 0.94 with statistical significance at the level of .01.